G18(P) Our chronic fatigue syndrome/encephalomyelitis service is nice, but is it patient friendly? experience of going beyond audit. (12th March 2018) - Taylor, AM; Man, J; Parish, EJ; Segal, T
Abstract : Aim: To assess the quality of diagnosis and management of Chronic Fatigue Syndrome (CFS)/Encephalomyelitis (ME) in a tertiary Service against NICE guidelines, along with views of the young people assessed. Methods: A retrospective audit of patients referred to the CFS/ME service over a 12 month period (December 2014-December 2015 chosen to allow time for follow up). Case notes and electronic records were reviewed for baseline demographics, NICE criteria (Guideline CG53) and additional information. Patients and/or their parents were contacted for feedback by telephone using a structured transcript and standardised Friends and Family questionnaire. Results: 30 patients were referred to the CFS/ME service, 3 of whom did not attend and were excluded from analysis. We assessed 5 NICE guideline criteria that relate to young people, all of which have a 100% standard. Three criteria focus on providing patients with relevant information. 86% of our patient records documented advice on symptom management, 71% on work/education, and 43% on general principles of CFS/ME. The service was 100% compliant with criterion 4 (a diagnosis of CFS/ME should only be made when symptoms have persisted for 3 months). The final criterion assesses how many patients with mild/moderate CFS/ME are provided with cognitive behavioural therapy and/or graded exercise therapy; 73% of patients received one of these. 13 of the 27 young people/parents contacted for the Friends and Family questionnaire answered the telephone, 3 did not answer the questions. Of the 10 respondents (8 parents and 2 young people), 5 'agreed' with the statement 'this is a good service for my friends and family to be looked after in if they needed similar treatment or care', 3 'agreed a bit' and 2 'disagreed a lot'. Improvements focused on practicalities such as distance to the hospital, paucity of specialist services, and insufficient access to therapies. Conclusion: Our Service appropriately diagnoses young people with CFS/ME though compliance with NICE guidelines could be improved. We were disappointed that feedback was predominantly parental and wonder if an online or written Friends and Family test would facilitate hearing from young people themselves.